Public-Private Partnership as a Means of Activating Russian Tourism Potential - MEDVEDEVA, Natalia Vladimirovna; KABANOVA, Elena Evgenevna; ROGACH, Olga Vladimirovna; RYABOVA, Tatyana Mikhaylovna; FROLOVA, Elena Viktorovna (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The article presents the analysis of problems in modern tourism infrastructure in Russia. The results of the research show the limitations in attracting the tourist flow: underdeveloped tourism infrastructure, unsatisfactory condition of transport infrastructure, low quality of resort services, etc. The most effective mechanisms for modernizing objects of tourist attraction are sponsorship, patronage and public-private partnership. According to the representatives of local authorities, one of the prioritized ways of solving the problems is public-private partnership. Collaboration between local authorities and the entrepreneurship community will not only attract financial resources into the sector but will also allow the realization of joint projects for developing tourism infrastructure and tourism potential. As a result, the tourism industry developed in the framework of public-private partnership will become the most important means of activating Russian tourism potential and guaranteeing preservation, restoration and development of monuments of cultural and historical heritage, natural and recreational resources.